2005
DOI: 10.1177/0091270004273992
|View full text |Cite
|
Sign up to set email alerts
|

Studies to Investigate the Pharmacokinetic Interactions Between Ranolazine and Ketoconazole, Diltiazem, or Simvastatin During Combined Administration in Healthy Subjects

Abstract: The interactions of ranolazine, a new antianginal compound, with inhibitors and substrates of the CYP3A isoenzyme family were studied in 1 open-label and 4 double-blind, randomized, multiple-dose studies. In healthy adult volunteers, the authors sought (1) to determine the steady-state pharmacokinetics, safety, and tolerability of immediate- and sustained-release ranolazine with and without ketoconazole, diltiazem, or simvastatin and (2) to evaluate the effect of ranolazine on the pharmacokinetics of diltiazem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 18 publications
3
70
0
1
Order By: Relevance
“…17 The metabolite to ranolazine area under the curve from time 0 to 12 hours (AUC 12 ) ratio decreased 5.6-fold, 2.1-fold, and 4.6-fold for CVT-2512, CVT-2514, and CVT 2738, respectively. Adverse events, generally mild to moderate, but occasionally intolerable, such as headache, dizziness, and nausea, are significantly increased with the concomitant administration of ketoconazole 200 mg twice daily to ranolazine 1000 mg twice daily.…”
Section: Ranolazinementioning
confidence: 98%
“…17 The metabolite to ranolazine area under the curve from time 0 to 12 hours (AUC 12 ) ratio decreased 5.6-fold, 2.1-fold, and 4.6-fold for CVT-2512, CVT-2514, and CVT 2738, respectively. Adverse events, generally mild to moderate, but occasionally intolerable, such as headache, dizziness, and nausea, are significantly increased with the concomitant administration of ketoconazole 200 mg twice daily to ranolazine 1000 mg twice daily.…”
Section: Ranolazinementioning
confidence: 98%
“…It has been shown that diltiazem caused clinically significant drug-drug interactions by decreasing the elimination of substrates through the inhibition of CYP3A. 39,40) The cause of inhibition has been attributed to both diltiazem and its metabolites. Therefore, at high doses, CYP3A-mediated firstpass metabolism of diltiazem in the intestine and/or liver may be inhibited and/or saturated by itself and its metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…15 Diltiazem 180 mg/day and 360 mg/day increased steady-state plasma ranolazine concentrations 1.8-fold and 2.3-fold, respectively, when diltiazem was used concomitantly with ranolazine 1,000 mg twice daily. 1,15 Less potent CYP3A4…”
Section: Ss Disease and Drug Interactionsmentioning
confidence: 94%
“…1,15 Ketoconazole 200 mg twice daily increased average plasma ranolazine concentrations more than 3-fold when it was administered concurrently with extended-release ranolazine 1,000 mg twice daily. 15 Diltiazem 180 mg/day and 360 mg/day increased steady-state plasma ranolazine concentrations 1.8-fold and 2.3-fold, respectively, when diltiazem was used concomitantly with ranolazine 1,000 mg twice daily. 1,15 Less potent CYP3A4…”
Section: Ss Disease and Drug Interactionsmentioning
confidence: 99%